The problem doesn't make sense that you just said. You would have to use algebra. Use the inverses to cross out the variables from each side. Use the ones with like terms first. Then simplify. Calculators help with this type of problem.
22n + 2.
original problem: (m-24+9)-(3m-7n-12) distribute the negative sign: (m-24+9)+(-3m+7n+12) collect like terms: -2m+7n-3 that is as far as you can simplify this problem without knowing the values of m and n
Assuming you meant 7n (not just 7 at the end of your question) - first... simplify the equation. Numbers raised to powers get priority - so your new sum is... 5n - 64n + 25n + n + 7n.... This simplifies to... -26n
6m + 5n - 4m + 7n = 2m + 12n
(10, 2)
Add them together. They equal 2n.
-7n - 8 + 6 = 13 - 2 Add 2 to each side: -7n - 8 + 6 + 2 = 13 simplify: -7n = 13 n = -13/7 = -16/7
22n + 2.
63
original problem: (m-24+9)-(3m-7n-12) distribute the negative sign: (m-24+9)+(-3m+7n+12) collect like terms: -2m+7n-3 that is as far as you can simplify this problem without knowing the values of m and n
Assuming you meant 7n (not just 7 at the end of your question) - first... simplify the equation. Numbers raised to powers get priority - so your new sum is... 5n - 64n + 25n + n + 7n.... This simplifies to... -26n
6m + 5n - 4m + 7n = 2m + 12n
Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2
7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)
-7n2 + 74n + 33 = -7n2 + 77n - 3n + 33 = -7n*(n - 11) - 3*(n - 11) = =(-7n - 3)*(n - 11) = -(7n +3)*(n - 11)
This question as written can be taken two ways: 9m + 6n - 3m + 7n = 6m + 13n, or (9m + 6n) - (3m + 7n) = 9m + 6n - 3m - 7n = 6m - n
10n + 3 = 7n + 53n = 2n = 2/3